Base‐Free Dehydrogenation of Aqueous and Neat Formic Acid with Iridium(III) Cp*(dipyridylamine) Catalysts. Issue 1 (28th November 2018) - Wang, Shengdong; Huang, Haiyun; Roisnel, Thierry; Bruneau, Christian; Fischmeister, Cédric
Abstract: The selective dehydrogenation of formic acid by iridium(III) Cp*(dipyridylamine) catalysts is reported. The electron‐enriched catalyst [Ir III Cp*{(4‐dimethylaminopyridin‐2‐yl‐κ Ν )(pyridin‐2′‐yl‐κ Ν )amine}(OSO3 )] gave the best performances enabling the base free dehydrogenation of aqueous and neat formic acid. In both cases the reaction was selective with no carbon monoxide detectable. The Ir III complex demonstrated latent behavior, which may be of practical utility. Experimental results suggest an outer‐sphere interaction with the ligand. Abstract : No base, no problem : The selective dehydrogenation of formic acid by iridium(III) Cp*(dipyridylamine) catalysts is reported. An electron‐enriched Ir III complex gave the best performances, enabling base‐free dehydrogenation of aqueous and neat formic acid. Experimental results suggest an outer‐sphere interaction with the ligand.